Corporate Sustainability with the Contribution of Occupational Safety and Health - Plua Panta, Karina Alexandra; Morales Plua, Erika Alexandra; Tenelema Jiménez, Inés Elizabeth; Cabrera Moreira, Joel David (Espergesia, 2023)
Corporate sustainability has established itself as a fundamental pillar in the business world, providing companies with a competitive edge and adding value not only to the organizations themselves but also to their stakeholders and society at large. The primary aim of this research is to determine how advancements in workplace safety and health contribute to the sustainability of companies in Ecuador. Within this framework, the relationship between workplace safety and sustainability is of paramount importance. Through an in-depth literary review on corporate sustainability, with a particular emphasis on industrial safety, this study delves into the influence of workplace safety and health measures on business sustainability in Ecuador. Despite having a solid regulatory framework in place, a concerning non-compliance with regulations is detected in both the public and private sectors. Furthermore, there’s a noticeable gap in the training and awareness of workers regarding their rights when facing risks associated with their tasks. The conclusions highlight a significant disparity between theory and practical application, emphasizing the efficiency of management systems in Occupational Risk Prevention when properly implemented.Keywords: Sustainability; Companies; Industrial Safety; Occupational Risk.